(untitled) (Mustansiria Dental Journal, 2018)
This Study was done to compare between the digital and conventional panoramic radiography in the estimation of the distance between the crest of alveolar bone to the floor of maxillary sinus for proper dental implant in the posterior region of maxilla. Twenty patients were selected, they need multiple implants in different posterior edentulous regions of the maxilla, in the period from (January 2006-April 2006), 11 were males and 9 females of age between (37-52). All the patients were sending for digital and conventional panoramic radiographic examination. Comparison was done for the two types of radiographs with tracing chart readings of Friadent system for the measurement of implant length. The study shows that obvious differences between the digital and conventional panoramic radiography in comparison to tracing chart, while no differences were detected between the digital panoramic radiographs and the tracing chart. The study reported that the digital panoramic radiography is more accurate in estimation of proper bone measurement than conventional radiographs for precise dental implant selection.